Thymic epithelial tumors in a worldwide perspective: lessons from observational studies - Marino, Mirella; Salvitti, Tommaso; Pescarmona, Edoardo; Palmieri, Giovannella (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Progress in the understanding of thymic epithelial tumors (TET) are expected by improvement in tumor management as well as from discoveries in biological sciences. The data provided by the routine activity in health care of patients are as precious as the most advanced molecular investigation in tumor research. Therefore the recent JTD issue authored by the Chinese Alliance for Research in Thymomas (ChART), focused on thymic epithelial malignancy and covering a vast majority of clinical issues on these rare tumors, provides a summary of a longstanding experience on TET from the perspective of an authoritative scientific society/collaborative research group. Among the papers included in the ChART issue focusing on TET, an interesting paper from Zhu et al. is referring on the evaluation of clinicopathological features and outcome indicators in a TET series occurred at the Shanghai Chest Hospital (SCH) (1).